The Impact of Fiscal Policy on Investment in Libya (2000-2015) - Hamoudi, Mustafa Khalifa Thawadi El. (Scientific Research Publishing, Inc., 2016)
The fiscal policy effect on the investment spending in Libya is a study of the simple connection test which is a detailed study because it covers the period 2000-2015 and it selects the multiple regression model in a study to evaluate the effect of the fiscal policy on the investment spending by using the gross domestic product, the government spending. In this study, some of the related literature has been discussed and it has been done under three subtitles: a theoretical, experimental and analytical review and study. The study shows that the gross domestic product has a positive effect on the investment spending in Libya and growth in gross domestic product (GDP) will lead to the expansion of investment spending in Libya during the study period (2000-2015).
Keywords: 8. Economic growth; 1. No poverty; 3. Good health